The Effect of Some Ground Training Variables on the 35-meter Distance and Achievement in Swimming Activities - Ahmad Kazim, Mustafaa; Hameed Shaker Habeeb, Ali; Hasan Hamash , Ali (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to know the effect of some vocabulary of the ground training on developing time of (35 m) distance and achievement. For the purpose of achieving the research goal, the researcher chose (10) swimmers ages (15-16 years) in a random manner, and they were divided into two groups, control and experimental, each consisting of (5) swimmers. The control group implemented the paragraphs of the water training program prepared by its trainer; the experimental group implemented the vocabulary of the training program prepared by the researcher. For the purpose of achieving the research goals, the researcher conducted pretests on the research sample before and after the 12-week training period by three training units per week, and the results achieved were statistically analyzed for both groups, where the researcher found the time of the distance (53 m) has been extended It was seen by both groups, but the group that carried out the vocabulary of the water training prepared by the researcher was the best, so the researcher recommends that you include the appropriate water exercises with the usual ground exercises in the way of the Plyometric exercises, which can achieve a positive impact on the time of the distance of (35 m) in the activities Olympic swimming (free and butterfly), as it is a method that serves the nature of the working muscles during performance.